4-E (environmental, economic, energetic and exergetic) analysis of slow pyrolysis of lignocellulosic waste. (December 2020) - Torres, Erick; Rodriguez-Ortiz, Leandro A.; Zalazar, Daniela; Echegaray, Marcelo; Rodriguez, Rosa; Zhang, Huili; Mazza, Germán
Abstract: The bio-waste slow pyrolysis process is assessed by four indicators to determine its energetic, exergetic, economic and environmental performance. The influence of the pyrolysis temperature (300–800 °C) on these parameters, but also on the biochar, bio-oil and gas production, is analysed. The biochar yield decreased 10.5% and the gas yield increased 17.2% between 300 and 800 °C. The bio-oil yield increased about 2.1% between 300 and 500 °C and decreased about 8% between 500 and 800 °C. Within the temperature range 300–800 °C, the H2, CO and CH4 molar fractions increased 51.4, 6.6 and 0.3%, respectively. CO2 content decreased about 58.3%. The exergy efficiency varied between 81.16 and 85.33% in this temperature range. The exergy-based economic factor revealed that 15.38–19.16% of the total cost was associated with the exergy destruction. The environmental impact was lower at higher temperatures. The recommended temperature range is 300–400 °C to produce biochar, and temperatures of over 700 °C to produce gas. When the interest focus is on the bio-oil, it is recommended to work close to 500 °C. Graphical abstract: Image 1 Highlights: Thermodynamic equilibrium model was applied to predict biochar, bio-oil and gas yields. The bio-oil yield showed a maximum at 500 °C. H2, CO and CH4 contents in the pyrolysis gas increased with the pyrolysis temperature. The exergy efficiency varied between 81.16 and 85.33%. 15.38–19.16% of the total cost is associated with exergy destruction.